2017
DOI: 10.3390/ijgi6110363
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Parallel Spatial Interpolation Algorithm for Massive LiDAR Point Clouds on Heterogeneous CPU-GPU Systems

Abstract: Nowadays, heterogeneous CPU-GPU systems have become ubiquitous, but current parallel spatial interpolation (SI) algorithms exploit only one type of processing unit, and thus result in a waste of parallel resources. To address this problem, a hybrid parallel SI algorithm based on a thin plate spline is proposed to integrate both the CPU and GPU to further accelerate the processing of massive LiDAR point clouds. A simple yet powerful parallel framework is designed to enable simultaneous CPU-GPU interpolation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Manuscript to be reviewed Computer Science analysis (Zhang et al, 2017), urban growth simulation (Guan et al, 2016), Delaunay Triangulation (DT) for GIS (Coll and Guerrieri, 2017), spatial interpolation (Wang et al, 2017;Cheng, 2013;Mei, 2014;Mei et al, 2017;Mei, 2014;Ding et al, 2018b), and image processing (Wasza et al, 2011;Lei et al, 2011;Yin et al, 2014;Wu et al, 2018).…”
Section: /29mentioning
confidence: 99%
“…Manuscript to be reviewed Computer Science analysis (Zhang et al, 2017), urban growth simulation (Guan et al, 2016), Delaunay Triangulation (DT) for GIS (Coll and Guerrieri, 2017), spatial interpolation (Wang et al, 2017;Cheng, 2013;Mei, 2014;Mei et al, 2017;Mei, 2014;Ding et al, 2018b), and image processing (Wasza et al, 2011;Lei et al, 2011;Yin et al, 2014;Wu et al, 2018).…”
Section: /29mentioning
confidence: 99%
“…They demonstrated performance improvements over a serial version on a CPU through a series of tests, and achieved speedup from 10 to 100. Wang et al [10] proposed a hybrid parallel spatial interpolation algorithm executed on both the CPU and GPU to increase the performance of massive LiDAR point clouds processing. Their experimental results have shown that their hybrid CPU-GPU solution outperforms the CPU-only and GPU-only implementations.…”
Section: Remote Sensing and Dta Algorithms Implementation On A Gpumentioning
confidence: 99%
“…The space, time, and spectral resolution are constantly improved, which can be obtained with the TB level, and stored with PB. (2) Surveying and mapping data (Huang et al, 2016;Lu, Yuan, & Yu, 2017;Wang, Guan, & Wu, 2017): it generally includes geographical situation, industry geographic, thematic mapping data, such as 4D (DLG, DRG, DOM, DEM) digital products, land use, and other national basic surveying and mapping data. In recent years, with the 2013Big data giS Big data giS is from offline analysis/ model-driven/ simple visualization to dynamic/ data-driven/ visual analysis in real time generalized giS the characteristics of generalized giS and technical challenges from data collection and cleaning, management and integration, data analysis, and computing Lu and Zhang (2014) Open giS…”
Section: Big Spatial Datamentioning
confidence: 99%